PHYSICOCHEMICAL CHARACTERISTICS AND ANTIMICROBIAL ACTIVITY TEST OF BACTERIOCIN FROM LACTIC ACID BACTERIA ISOLATE 15B ORIGINATED FROM BALI CATTLE COLON ISOLATION - Lestari, Ni Kadek Lyming; Suardana, I Wayan; Sukrama, I Dewa Made (Buletin Veteriner Udayana, 2019)
Lactic acid bacteria (LAB) is a group of Gram-positive bacteria, in shape of coccus or bacilli and catalase-negative and also have the ability to produce lactic acid. LAB is also a microorganism which is not toxic and has the ability to produce antimicrobial compounds, known as bacteriocins. This research aimed to find out the physicochemical characteristic and the antimicrobial activities of bacteriocin isolated from isolates 15B originated from the bali cattle’colon. This study began by reculturing of isolates 15B and followed by cultivating the isolates, isolating, producing, and precipitating of bacteriocins. The physical and chemical properties of the bacteriocins were also tested before, antimicrobial activity test was conducted. The result of the cultivation showed that isolates 15B is a lactic acid bacteria characterized by the result of Gram staining as a Gram positive, catalase negative and grown on anaerobic condition. The result of chemical test, showed that bacteriocins producing isolates 15B were positive on Ninhydrin test, negative on Molisch test, and positive on Lowry test with 0,11 µg/ml concentration. Physical properties test using SDS PAGE showed negative result and antimicrobial activity test showed that the bacteriocin from isolates 15B has 35,82% effectiveness of inhibition.